Prospective, single-center cohort study analyzing the efficacy of complete laparoscopic resection on recurrent hepatocellular carcinoma. Issue 1 (December 2016) - Zhang, Jie; Zhou, Zhong-Guo; Huang, Zhong-Xi; Yang, Ke-Li; Chen, Jian-Cong; Chen, Jin-Bin; Xu, Li; Chen, Min-Shan; Zhang, Yao-Jun
Abstract Background Laparoscopic hepatectomy is increasingly being used to treat hepatocellular carcinoma (HCC). However, few studies have examined the treatment of recurrent HCC in patients who received a prior hepatectomy. The present prospective study compared the clinical efficacy of laparoscopic surgery with conventional open surgery in HCC patients with postoperative tumor recurrence. Methods We conducted a prospective study of 64 patients, all of whom had undergone open surgery once before, who were diagnosed with recurrent HCC between June 2014 and November 2014. The laparoscopic group (n = 31) underwent laparoscopic hepatectomy, and the control group (n = 33) underwent conventional open surgery. Operation time, intraoperative blood loss, surgical margins, postoperative pain scores, postoperative time until the patient could walk, anal exsufflation time, length of hospital stay, and inpatient costs were compared between the two groups. The patients were followed up for 1 year after surgery, and relapse-free survival was compared between the two groups. Results All surgeries were successfully completed. No conversion to open surgery occurred in the laparoscopic group, and no serious postoperative complications occurred in either group. No significant difference in inpatient costs was found between the laparoscopic group and the control group (P = 0.079), but significant differences between the two groups were observed for operation time (116.7 ± 37.5 vs. 148.2 ± 46.7 min, P = 0.031), intraoperative blood loss (117.5 ± 35.5 vs. 265.9 ± 70.3 mL, P = 0.012), postoperative time until the patient could walk (1.6 ± 0.6 vs. 2.2 ± 0.8 days, P < 0.05), anal exsufflation time (2.1 ± 0.3 vs. 2.8 ± 0.7 days, P = 0.041), visual analogue scale pain score (P < 0.05), postoperative hepatic function (P < 0.05), and length of hospital stay (4.5 ± 1.3 vs. 6.0 ± 1.2 days, P = 0.014). During the 1-year postoperative follow-up period, 6 patients in each group had recurrent HCC on the side of the initial operation, but no significant difference between groups was observed in the recurrence rate or relapse-free survival. In the laparoscopic group, operation time, postoperative time until the patient could walk, anal exsufflation time, and inpatient costs were not different (P > 0.05) between the patients with contralateral HCC recurrence (n = 18) and those with ipsilateral HCC recurrence (n = 13). However, intraoperative blood loss was significantly less (97.7 ± 14.0 vs. 186.3 ± 125.6 mL, P = 0.012) and the hospital stay was significantly shorter (4.2 ± 0.7 vs. 6.1 ± 1.7 days, P = 0.021) for the patients with contralateral recurrence than for those with ipsilateral recurrence. Conclusions For the patients who previously underwent conventional open surgical resection of HCC, complete laparoscopic resection was safe and effective for recurrent HCC and resulted in a shorter operation time, less intraoperative blood loss, and a faster postoperative recovery than conventional open surgery. Laparoscopic resection was especially advantageous for the patients with contralateral HCC recurrence.